A crítica do fenômeno das "ONGs" no Brasil: uma análise da atuação na política social de proteção à criança e ao adolescente em Recife - Rios Junior, Ademir Vilaronga (2013)
The aim of this study was to analyze the performance and the strategic place of Non-Governamental Organizations/NGOs in the consolidation of social policies, in particular in health care provision for children and adolescents in Recife, as well as chart your profile. The study had the delimitation sample eighty-eight (out of 100) organizations registered in COMDICA. To achieve the objectives of this study, from a critical perspective, we conducted an exploratory, basic qualitative and quantitative. So, it was possible to understand the dynamics of "NGOs" in the current situation and its functionality in the production and reproduction of social life, through the analysis of the expressions of the socio-historical that underlie the structure of these organizations, especially in the context of neoliberalism in Brazil. We start by reading the theoretical and methodological categories (civil society and State) and concepts ("NGO" and "third sector"). The organizations studied have a mission to ensure the full protection of children and adolescents as executing those policies through public and private partnerships. 46% of the analyzed entities were founded after 1990. They serve fifty thousand users. The action of these private organizations stands out in the execution of basic protection policy Welfare. Identified two main conceptions in the approach of this phenomenon: the design (neo) liberal, who put the "NGOs" as the best option for the implementation of policies and removes the functions of the state and the market in relation to compliance with the manifestations of the "social question", and the critical-materialist perspective, we understand this phenomenon as a byproduct of "neoliberal strategy." This research will approach from this standpoint.Therefore, it was identified that "NGOs" as "representatives" of civil society, take the spaces of contention and a representative to defend their "assisted" posture, but can not identify such an attitude contribute to human emancipation and policies of service users.There is a new political stance against the state, marked by "partnership", and outsourcing services. Their position in the relations of forces is in order to ensure social harmony, helping to focus and fragmentation of social policies, and its role in strengthening the social struggles to defend and conquer right now does not matter, as in decades previous, or imply needs before idealized social change. Thus, it was concluded that the placement of "NGOs" in Recife, currently contributes only playing a system that denies the constitutional rights and citizenship - in its broad sense - contributing to the process of despoliticization of social struggles and people's organizations, leaving the users even more unprotected and alienated. Regarding the political articulation of these organizations in the city, there is a process of despoliticization of the struggles in defense of the rights of children and adolescents. Organizations, by putting only as executing projects no longer take center stage in the relationship of forces in defense of universal rights. They are not, currently, as a movement of struggle strengthened to ensure better political and social conditions for children in Recife.